60th birthday of ‘A Behavioral Theory of the Firm’: a review of the relational concepts and recommendations for future research - Hagen, Moritz; Su, Wenjia; Junge, Sebastian (Management Review Quarterly, 2023)
This year, we celebrate the sixtieth anniversary of ‘A Behavioral Theory of the Firm’ (BTF) (Cyert and March in A behavioral theory of the firm, Prentice Hall, Englewood Cliffs, 1963), which central ideas and concepts are fundamental to almost all theoretical and empirical work focusing on organizational decision-making. In particular, the four underlying relational concepts of BTF: (1) quasi resolution of conflict, (2) uncertainty avoidance, (3) problemistic search, and (4) organizational learning provide theoretical explanation for firms’ decision-making behavior. However, as literature has grown, focus of the studies and application of the concepts are becoming increasingly fragmented, leading to parallel and decoupled insights rather than cohesive and complementary explanations. We conduct a systematic literature review of 114 publications in top-ranked journals to provide a deeper understanding of the applications of BTF’s four relational concepts and their interrelation. Reviewing and synthesizing extant literature, we identify seven different organizational decision areas in which mainly two relational concepts, problemistic search and organizational learning, are applied to explain specific firm behaviors. The relational concept of quasi resolution of conflict and uncertainty avoidance seem underrepresented or almost neglected in the BTF-related research. Furthermore, we provide an integrative process framework connecting the four relational concepts and related research insights, and thereby, highlight opportunities for future research.
Created from Fastlane, Scopus look-up
Keywords: A Behavioral Theory of the Firm; Decision-making; Organizational learning; Problemistic search; Quasi resolution of conflict; Uncertainty avoidance

Beyond politics: How organizational political ideology shapes organizational resilience through exploration in the face of Covid-19 - Su, Wenjia; Hoßnofsky, Verena; Junge, Sebastian (European Academy of Management (EURAM) - Fostering Innovation To Address Grand Challenges, 2024)

Red or blue survival of Covid-19: Organizational political ideology, exploration, and resilience - Su, Wenjia; Hoßnofsky, Verena; Junge, Sebastian (84th Annual Meeting of the Academy of Management - Innovating for the Future, 2024)

The red or blue escape route: Does organizational political ideology affect organizational resilience? - Su, Wenjia; Hoßnofsky, Verena; Junge, Sebastian (40th EGOS Colloquium - Crossroads for Organizations: Time, Place and People, 2024)

Unlocking the recipe for organizational resilience: A review and future research directions - Su, Wenjia; Junge, Sebastian (European Management Journal, 2023)
In these challenging times of climate change, pandemic, and war, research on organizational resilience has gained significant momentum. The purpose of our review is to examine how adverse events and antecedents at the individual, group, organizational, and network levels affect organizational-resilience processes and their outcomes. Based on a systematic search in 53 top-ranked journals over a period of 25 years from 1997 to 2022 and an additional backward reference search, we conduct a framework-based literature review of 127 publications. We find that the form of the adverse event (i.e., its emergence, novelty, and severity) determines the resilience process and underlying actions. To address the multilevel facets of organizational resilience, we integrate a comprehensive array of antecedents at the individual, group, organizational, and network levels, and show that their influence on resilience processes and outcomes can be beneficial or detrimental depending on the context. We highlight research opportunities along our framework (antecedents, process, and outcomes) and derive a set of propositions.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Adversity; Crisis; Disaster; Organizational resilience